Analisis Permintaan Dan Biaya Differensial Terhadap Keputusan Menerima Atau Menolak Pesanan Khusus Pada Konveksi Djogja Latansa - Nurhidayat, Ahmad; Husain, Muchammad Ikbal; Wijaya, Ajeng Retno (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
Clothing or apparel is a fundamental human need. Clothes or clothing can show the identity of a product or image of a convection business. Convection business is a fashion business that produces a variety of men's clothes or student uniforms in public and private universities. At certain times, Konveksi's business can obtain abundant orders from consumers. This will make the reason for the making of T-shirts and apparel to increase. This study aims to analyze the special requests and costs associated with making decisions in accepting special orders. This research uses quantitative descriptive research with object research on Djogja Latansa. Data collection techniques used in this study were the Observation, Interview, and Literature Review (Library Research) and the data analysis technique used differential analysis. The results of this study indicate that the convection business has carried out an analysis of demand and differential costs and received special orders. Business actors ask for differential cost analysis on decision making, to be more careful in sorting incoming order requests